Biosynthesis of Silver Nanoparticles from Rhododendron arboreum for Metal Sensing, Antibacterial Assessment, and Photocatalytic Degradation. (15th June 2022) - Phuyal, Sitaram; Lamichhane, Ganesh; Gupta, Aakash; Khadayat, Karan; Adhikari, Anup; Marahatha, Rishab; Khadka, Sujan; Parajuli, Niranjan
Abstract : The nanomaterial industry has focused on green synthetic methods to avoid unpleasant compounds produced during manufacturing, offering eco-friendly, sustainable, and nature-derived alternative methods. In this study, silver nanoparticles (Ag NPs) have been synthesized from an aqueous extract of the leaves of Rhododendron arboreum, where the pH of the reaction mixture is found to be crucial. The reaction progress monitored using the UV-Vis spectrophotometer displayed a strong absorption band at 425 nm at pH 9, suggesting an optimum pH for the synthesis. The Ag NPs thus synthesized were characterized using instrumental techniques. The attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy showed the presence of phytoconstituents in the aqueous extract, which are believed to be responsible for reducing Ag + ions to Ag NPs and capping agents on its surface for stability. X-ray diffraction (XRD) showed a highly crystalline nature, and energy-dispersive X-ray (EDX) demonstrated the presence of metallic silver. The scanning and transmission electron microscopy (SEM and TEM, respectively) revealed crystalline morphology and monodisperse Ag NPs of sizes ranging from 23 to 41 nm. Furthermore, the metal-sensing activity of biosynthesized Ag NPs was evaluated using various metal ions; they were utilized for highly selective and sensitive colorimetric detection of Hg 2+ in an aqueous medium among various metal ion solutions tested with the detection limit of 0.5 mM using the UV-Vis spectrophotometer. Similarly, they were also shown to be effective for the nanocatalytic activity for degradation of methylene blue dye up to 81%. These studies demonstrated Ag NPs as potential candidates for selective detection of mercury in water resources, a tool for sensing the heavy metals and degradation of synthetic dye from industrial effluents in wastewater treatment. Having the high surface-to-volume ratio and size-dependent functionality of Ag NPs, further optimization studies at micromolar and nanomolar detection limits will avail its better industrial utilization. Moreover, biologically mediated Ag NPs can also exhibit good antimicrobial activity against Staphylococcus aureus and Escherichia coli .